2019
DOI: 10.3390/antiox8010009
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase (Rboh) Activity is Up Regulated during Sweet Pepper (Capsicum annuum L.) Fruit Ripening

Abstract: In plants, NADPH oxidase (NOX) is also known as a respiratory burst oxidase homolog (Rboh). This highly important enzyme, one of the main enzymatic sources of superoxide radicals (O2•−), is involved in the metabolism of reactive oxygen and nitrogen species (ROS and RNS), which is active in the non-climacteric pepper (Capsicum annuum L.) fruit. We used sweet pepper fruits at two ripening stages (green and red) to biochemically analyze the O2•−-generating Rboh activity and the number of isozymes during this phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 62 publications
0
53
0
Order By: Relevance
“…Given that pepper fruit ripening is subject to nitro‐oxidative stress (Corpas et al , Chu‐Puga et al ), to gain further insight into the regulation of NADP‐ME activity in pepper fruit, the effect of increasing concentrations of NO and peroxynitrite donors (Begara‐Morales et al , , Chaki et al , de Freitas‐Silva et al , Mun et al ) was also evaluated. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Given that pepper fruit ripening is subject to nitro‐oxidative stress (Corpas et al , Chu‐Puga et al ), to gain further insight into the regulation of NADP‐ME activity in pepper fruit, the effect of increasing concentrations of NO and peroxynitrite donors (Begara‐Morales et al , , Chaki et al , de Freitas‐Silva et al , Mun et al ) was also evaluated. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we found that the nitric oxide (NO) metabolism is significantly affected during sweet pepper fruit ripening (Chaki et al , Corpas et al ) and, more recently, that NADP‐ICDH is inhibited by both H 2 S and NO, suggesting that NADPH generation is compromised during pepper ripening (Muñoz‐Vargas et al ). We have also shown that NADPH oxidase (Rboh) activity increases during the ripening process (Chu‐Puga et al ), thus highlighting the important role played by NADPH in the fruit physiology. This study aims to analyze the other plant NADPH‐generating systems (G6PDH, 6PGDH and NADP‐ME) during ripening and to evaluate how their activity is affected by H 2 S.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations